Recent Trends and Challenges in Campus placements of Engineering Institutions - Neelakantappa, B. B.; Suresh Babu, C. S.; Boregowda, Uma; Vinod, A. M. (Journal of Engineering Education Transformations, 2018)
Campus placement is a buzzword these days in most of the university colleges, especially in engineering institutions. Students, parents, faculty and even the management consider the placement as a vital parameter in judging the quality of the institution. Further from the students’ perspective, it is good and safe to get placed in some company in the campus itself. The reasons are twofold. Firstly, high competition in off-campus placements and the second is the recession due to economic and business fluctuations in a global scenario, which obviously decreases the number of employment opportunities. In an attempt to address these challenges, few innovative steps were taken to increase the number of placements. The outcome of this resulted in all time record placements in our institution. In this paper, challenges faced in placements and certain remedial measures to meet the same are discussed.